A conformationally stable contorted hexabenzoovalene - Baumgärtner, Kevin; Dreuw, Andreas; Rominger, Frank; Mastalerz, Michael (Angewandte Chemie, 2016)
Contorted two-dimensional aromatic molecules are fascinating synthetic targets because they are molecular “cutouts” of nonplanar graphene structures, fullerenes, or carbon nanotubes. In most cases, the curvature is introduced by the implementation of either five-, seven-, or eight-membered rings into the fused aromatic plane. Curvature can also be generated for two-dimensional systems consisting of six-membered rings exclusively, by the introduction of cove or fjord regions. The synthesis of a polycyclic aromatic hydrocarbon (PAH) that contains two peripheral triptycene units and six tert-butyl substituents is described.